Influence of TEMPO-oxidised cellulose nanofibrils on the properties of filler-containing papers - Lourenço, Ana F. (2016)
In this work, cellulose nanofibrils (CNF) were produced from a Eucalyptus globulus bleached kraft pulp by TEMPO-mediated oxidation and mechanical homogenisation, and their effects in papermaking, namely filler flocculation and retention, dry and wet-web strength and structural properties, were studied in detail. Cellulose nanofibrils possessing 0.6 mmol/g carboxyl groups and a degree of polymerisation (DP) of ca. 550 were found to promote filler flocculation and retention in the fibre mat, whereas the same amount (3 wt%) of CNF having 1.5 mmol/g of carboxyl groups, a DP of ca. 200 and a similar mean diameter exhibited the opposite effect. These results were interpreted with the help of flocculation studies of precipitated calcium carbonate (PCC) in the presence of CNF carried out by laser diffraction spectrometry. In addition, the mechanical and structural properties of the handsheets were analysed, revealing that the less charged CNF led to more closed matrices and, even increasing the filler retention, had a positive role on the tensile strength. A bonding mechanism among eucalypt fibres, PCC, CNF and a linear cationic polyacrylamide is proposed, consistent with the flocculation, retention and paper strength and structural property results. It is concluded that, to be used in papermaking, the CNF must not have a high charge (or a small length) to be able to flocculate the filler particles and, at the same time, to increase the filler-to-cellulosic fibres bonding. A complementary study on the wet-web resistance of handsheets produced with the less charged CNF was conducted for moisture contents between 10 and 70%, showing that these CNF can significantly improve the handsheet wet tensile strength (nearly 100%) even for water contents above 50%. The use of CNF in the paper machine may thus contribute, through the higher wet-web tensile resistance, to reducing breaks and increasing the operating speeds and, through the higher filler retention, to important fibre and cost savings.